When does ostracism lead to turnover intention? The moderated mediation model of job stress and job autonomy - Koon, Vui Yee*; Tee, Yen Hwa (Elsevier, 2020)
The current study explored the mediating and moderating processes through which social exclusion or ignorance causes employee behavioural outcomes in a workplace. Based on the conservation of resources (COR) theory, this study investigated the effect of perceived workplace ostracism on turnover intention as mediated by job stress and moderated by job autonomy among a sample of 144 employees from the consumer services sector in Malaysia. The results suggest that employees’ perceived workplace ostracism leads to job stress, which in turn leads to negative behavioural outcomes such as turnover intention. Job autonomy was also found to have moderated the mediated relationship, whereby the relationship was stronger with low levels of job autonomy. The results provided some practical implications, highlighting the importance of addressing workplace ostracism and promoting job autonomy.